IbM MGMP IPA SMP KOTA YOGYAKARTA DAN KABUPATEN SLEMAN DALAM MENGEMBANGKAN LKPD YANG DIGUNAKAN PADA STRATEGI PEMBELAJARAN UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK MELALUI PENDEKATAN IDEATIONAL LEARNING - Jumadi, -; Salirawati, Das; Subali, Bambang (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
This commuity service aims to improve (1) the professionalism of teachers in schools in developing ideational learning based worksheet in order to improve the creativity of the learners; (2) the ability of the teachers to develop the test items measuring the creativity as well as the performance using QUEST program. This community service activities was carried out through a series of activities such as lectures, question and answer, discussion, practice, and mentoring. Participants were 15 teachers from subject teachers deliberation of Sleman, and 15 teachers of the subject teachers Deliberation of Yogyakarta. The materials were about deepening the concept/insights on ideational learning, forming ideational learning based worksheet, developing the ideational learning based evaluation tools and analyzing ideational learning based evaluation items. The results showthat the teachers are able to design the ideational evaluation worksheet. It is obtained from the performance of the desaining and drafting taskbook evaluation sheets. For the analysis, the participants are able to use the QUEST program analyzing multiple-choice and descriptions items in the worksheet